La protección social de la dependencia en España. Un modelo sui generis de desarrollo de los derechos sociales - Rodríguez Cabrero, Gregorio (Política y Sociedad, 2008)
Social and demographic changes related to informal care model as well as the new idea of social risk have lead to a social and political debate which has concluded at least in Spanish case in a new branch of the Welfare State, in many ways a synthesis of informal care Mediterranean tradition, Continental family vision and Nordic universalism. The new social protection model involves the construction of a complex institutional building. Its management, coordination, financing and evaluation constitutes a test of a mixed welfare which will show the conflicts between the new social protection model, the financial limits of Welfare State and the decentralization of social policies. The development of the Social protection Dependency Law from 2007 onwards it is crucial in relation to the future of Spanish social reform in the first half present century.